Search for new resonances in mass distributions of jet pairs using 139 fb −1 of pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector - The ATLAS collaboration; G. Aad; B. Abbott; D. C. Abbott; A. Abed Abud; K. Abeling; D. K. Abhayasinghe; S. H. Abidi; O. S. AbouZeid; N. L. Abraham; H. Abramowicz; H. Abreu; et al. (Journal of High Energy Physics, 2020)
Abstract A search for new resonances decaying into a pair of jets is reported using the dataset of proton-proton collisions recorded at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector at the Large Hadron Collider between 2015 and 2018, corresponding to an integrated luminosity of 139 fb −1. The distribution of the invariant mass of the two leading jets is examined for local excesses above a data-derived estimate of the Standard Model background. In addition to an inclusive dijet search, events with jets identified as containing b-hadrons are examined specifically. No significant excess of events above the smoothly falling background spectra is observed. The results are used to set cross-section upper limits at 95% confidence level on a range of new physics scenarios. Model-independent limits on Gaussian-shaped signals are also reported. The analysis looking at jets containing b-hadrons benefits from improvements in the jet flavour identification at high transverse momentum, which increases its sensitivity relative to the previous analysis beyond that expected from the higher integrated luminosity.